THE IMPACT OF GREEN FINANCE AND SUSTAINABLE INVESTMENT ON CORPORATE FINANCIAL PERFORMANCE: A CROSS-SECTOR LITERATURE REVIEW - Putri Ridhotul Uliyah; Siti Hajar; Junaidi Junaidi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study analyzes the impact of green finance and sustainable investment on corporate financial performance through a comprehensive cross-sector literature review. The increasing global awareness of environmental issues has encouraged companies to adopt sustainable finance practices. This study synthesizes findings from ten recent peer-reviewed journal articles (2022-2025) covering a wide range of geographic and sectoral focuses. The review results show that green finance and sustainable investment tend to have a positive impact on corporate financial performance, mainly through lowering the cost of capital, enhancing reputation, and encouraging green innovation. These mechanisms vary across sectors, with high-environment risk sectors focusing on risk management, while services and finance sectors place greater emphasis on transparency and investor attraction. Challenges such as high upfront costs, lack of standards, and greenwashing risks remain, but opportunities from market growth, regulatory support, and technological innovation are significant. This study provides important insights for policymakers, investors, and companies in formulating effective sustainability strategies.